2016
DOI: 10.1007/s00421-016-3364-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower thermal sensation in normothermic and mildly hyperthermic older adults

Abstract: Skin warmth detection thresholds at forearm and whole body warmth perception under NT and HT and skin cold detection thresholds at forearm under NT deteriorated with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This was especially evident for the period when applying the absorbent pads and stretch clothing to the skin, as the younger group reported a significant rise in thermal sensation and became more uncomfortable, whereas the older group did not. The inability to report a change in thermal sensation and comfort when adding a layer of clothing highlights the vulnerability of older individuals in warm conditions and supports the previous evidence of a reduced whole body thermal sensitivity (Natsume et al 1992;Taylor et al 1995;Tochihara et al 2011;Takeda et al 2016) and thermal comfort (Natsume et al 1992;Taylor et al 1995;Waldock et al 2018) in the aged.…”
Section: Gastrointestinal Temperature Thermal Sensation and Comfortsupporting
confidence: 80%
“…This was especially evident for the period when applying the absorbent pads and stretch clothing to the skin, as the younger group reported a significant rise in thermal sensation and became more uncomfortable, whereas the older group did not. The inability to report a change in thermal sensation and comfort when adding a layer of clothing highlights the vulnerability of older individuals in warm conditions and supports the previous evidence of a reduced whole body thermal sensitivity (Natsume et al 1992;Taylor et al 1995;Tochihara et al 2011;Takeda et al 2016) and thermal comfort (Natsume et al 1992;Taylor et al 1995;Waldock et al 2018) in the aged.…”
Section: Gastrointestinal Temperature Thermal Sensation and Comfortsupporting
confidence: 80%
“…However, whether there are age-related alterations in the perception of hyperthermia (i.e., increases in core temperature) remains unclear. Takeda et al recently found that older adults have a greater temperature threshold for the perception of warmth during both skin warming and mild whole-body heating, providing evidence for a reduced perception of hyperthermia in aging (60). However, using an experimental paradigm similar to the one used herein, Schlader et al found no age-related reductions in the perception of hyperthermia (48).…”
Section: Discussionmentioning
confidence: 61%
“…Behavioural temperature regulation may play a critical role in initiating heat relief strategies during heat waves, working alongside the specific physiological mechanisms to that target population when attempting to mitigate adverse heat health outcomes. Whereas age-related alterations in thermal perception have been identified in adults ( Takeda et al, 2016 ; Baquero and Forcada, 2022 ), there is limited evidence available for children and adolescents. The present study demonstrates that self-reported thermal sensation and comfort are similar between children and adults during periods when a local heat alert is broadcasted.…”
Section: Discussionmentioning
confidence: 99%